Lenalidomide Maintenance with or without Prednisone in Newly Diagnosed Myeloma Patients: A Pooled Analysis - Bonello, Francesca; Pulini, Stefano; Ballanti, Stelvio; Gentile, Massimo; Spada, Stefano; Annibali, Ombretta; Omedé, Paola; Ronconi, Sonia; Cangialosi, Clotilde; Podda, Luigi; Palmas, Angelo; Malfitano, Alessandra; et al. (Cancers, 2019)
: We conducted a pooled analysis of two phase III trials, RV-MM-EMN-441 and EMN01, to compare maintenance with lenalidomide-prednisone vs. lenalidomide in newly diagnosed transplant-eligible and -ineligible myeloma patients. Primary endpoints were progression-free survival, progression-free survival 2 and overall survival with both regimens. A secondary aim was to evaluate the impact of duration of maintenance on overall survival and on outcome after relapse. A total of 625 patients (lenalidomide-prednisone arm, n = 315; lenalidomide arm, n = 310) were analyzed. The median follow-up was 58 months. Median progression-free survival (25 vs. 19 months; p = 0.08), progression-free survival 2 (56 vs. 49 months; p = 0.9) and overall survival (73 months vs. NR; p = 0.08) were not significantly different between the two arms. Toxicity profiles of lenalidomide-prednisone and lenalidomide were similar, with the exception of neutropenia that was higher in the lenalidomide arm (grade ≥ 3: 9% vs. 19%, p < 0.001), without an increase in the rate of infections. Overall survival (median NR vs. 49 months, p < 0.001), progression-free survival from relapse (median 35 vs. 24 months, p = 0.004) and overall survival from relapse (median not reached vs. 41 months, p = 0.002) were significantly longer in patients continuing maintenance for ≥2 years. We showed that the addition of prednisone at 25 or 50 mg every other day (eod) to lenalidomide maintenance did not induce any significant advantage.
Keywords: multiple myeloma; maintenance; prednisone; newly diagnosed; lenalidomide